KOMPETENSI PROFESIONAL GURU KELAS B DI RA ASSAFI’IYAH MADA JAYA WAY KHILAU PESAWARAN - Aulia Rahma (Institut Agama Islam Negeri Metro, 2021)
Teacher professional competence is the skills, abilities, skills of a teacher in the teaching and learning process. This research was conducted to find out how the professional competence of class B teachers at RA Assafi'iyah Mada Jaya Way Khilau Pesawaran, which includes the professional competence of teachers in improving learning outcomes, managing classes, using learning media, and assessing learning outcomes. This research uses field research (Field Research). To collect data the author uses 3 methods, namely: Interview / interview, observation, and documentation. Based on the research results, it shows that professional competence in improving learning outcomes is quite good, the teacher implements teaching and learning programs with the right strategy, and implements improvement programs to optimize children's development. In managing the class, it has not been maximized, such as the arrangement of the classroom layout and the learning atmosphere that is not conducive. In using learning media it is good enough. Teachers are skilled in utilizing everything that exists as a learning medium. In assessing learning outcomes, the teacher uses a variety of assessments that are tailored to the developmental aspects that they want to measure.